2005
DOI: 10.1248/bpb.28.1314
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Constituents in Plants 5. Evaluation of Some Mexican Plants for Their Trypanocidal Activity and Active Constituents in the Seeds of Persea americana

Abstract: As a preliminary screening test for the trypanocidal activity against epimastigotes of Trypanosoma cruzi in vitro, we examined some crude extracts of Mexican medicinal plants. 2)T. cruzi is the etiological agent for Chagas' disease (American trypanosomiasis), one of the most serious protozoan diseases in Latin America. Then we started on identification of the principal compounds of the active extracts seeking new chemotherapeutic agents for Chagas' disease. Lignans 2) from Guaco (roots of Aristolochia taliscan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 13 publications
2
26
0
3
Order By: Relevance
“…Our findings corroborate previously reported data on trypanocidal activity of Lippia species polar extracts (Abe et al 2005;Sülsen et al 2006). Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings corroborate previously reported data on trypanocidal activity of Lippia species polar extracts (Abe et al 2005;Sülsen et al 2006). Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 .…”
Section: Discussionsupporting
confidence: 92%
“…Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 . On the other hand, Abe et al (2005) reported in vitro activity of a methanol extract of Lippia dulcis leaves against trypomastigote forms of T. cruzi, with MIC (minimum inhibitory concentration) between 125 and 250 µg mL -1 . Similar inhibitory activities have been observed in our experiments against epimastigote forms of T. cruzi, with IC 50 between 20 and 375 µg mL -1 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The antitrypanosomal activity of these species has not been reported previously in the literature except in the case of Annona muricata, which has been used in the folk medicine of Nicaragua for diarrhea (Coee & Anderson, 1996) and for fever in Colombia (Blair et al, 1991). Its antitrypanosomal activity against epimastigotes was reported previously (Abe et al, 2005). The 95% ethanol extract of seeds of Annona cherimola Mill.…”
Section: Antitrypanosomal Activitymentioning
confidence: 52%
“…Se ha reportado que el extracto de la hoja de B. dracunculifolia, a una concentración de 3 mg/mL, produjo 100% de lisis de formas tripomastigotes de T. cruzi (13) ; los extractos y fracciones de A. amazonicus mostraron lisis de las formas tripomasigotes de T. cruzi in vitro (14) ; otros investigadores también han demostrado el efecto tripanocida de diversos extractos vegetales (10,15,16) , así como de diversas estructuras terpénicas contra uno o todos los estadíos de T. cruzi (17)(18)(19)(20) . También han mostrado efecto tripanocida algunos alcaloides (21)(22)(23) , flavonoides (24)(25)(26) , lignanos (27) y artemisininas (28) .…”
Section: Discussionunclassified